Impact of coronavirus disease 2019 (COVID-19) on US Hospitals and Patients, April–July 2020. (19th January 2022) - Sapiano, Mathew R. P.; Dudeck, Margaret A.; Soe, Minn; Edwards, Jonathan R.; O'Leary, Erin N.; Wu, Hsiu; Allen-Bridson, Katherine; Amor, Agasha; Arcement, Rashad; Chernetsky Tejedor, Sheri; Dantes, Ray; Gross, Cindy; et al.
Abstract: Objective: The rapid spread of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) throughout key regions of the United States in early 2020 placed a premium on timely, national surveillance of hospital patient censuses. To meet that need, the Centers for Disease Control and Prevention's National Healthcare Safety Network (NHSN), the nation's largest hospital surveillance system, launched a module for collecting hospital coronavirus disease 2019 (COVID-19) data. We present time-series estimates of the critical hospital capacity indicators from April 1 to July 14, 2020. Design: From March 27 to July 14, 2020, the NHSN collected daily data on hospital bed occupancy, number of hospitalized patients with COVID-19, and the availability and/or use of mechanical ventilators. Time series were constructed using multiple imputation and survey weighting to allow near–real-time daily national and state estimates to be computed. Results: During the pandemic's April peak in the United States, among an estimated 431, 000 total inpatients, 84, 000 (19%) had COVID-19. Although the number of inpatients with COVID-19 decreased from April to July, the proportion of occupied inpatient beds increased steadily. COVID-19 hospitalizations increased from mid-June in the South and Southwest regions after stay-at-home restrictions were eased. The proportion of inpatients with COVID-19 on ventilators decreased from April to July. Conclusions: The NHSN hospital capacity estimates served as important, near–real-time indicators of the pandemic's magnitude, spread, and impact, providing quantitative guidance for the public health response. Use of the estimates detected the rise of hospitalizations in specific geographic regions in June after they declined from a peak in April. Patient outcomes appeared to improve from early April to mid-July.